Donkey pericardium compares favorably with commercial xenopericardia used in the manufacture of transcatheter heart valves. Issue 10 (3rd July 2019) - Mao, Jifu; Rassoli, Aisa; Tong, Yiwei; Rouse, Elizabeth Nicole; Le‐Bel, Gaёtan; How, Daniel; Germain, Lucie; Fatouraee, Nasser; Zhang, Ze; Reed, Robert R.; Guidoin, Robert
Abstract: Transcatheter aortic valve implantation (TAVI) has gained considerable acceptance in the past decade due to its lower risks than conventional open‐heart surgery. However, the deformation and delamination of the leaflets during the crimping procedure have raised questions about the durability and long‐term serviceability of the pericardium tissue from which the leaflets are made. The collagen architecture, wall thickness and mechanical properties of donkey pericardium were investigated to assess its suitability as an alternative material for the manufacture of heart valves. Coupons sampled from different locations of donkey pericardium were investigated. Bovine, equine, and porcine pericardium specimens served as controls. The donkey pericardium had a similar surface morphology to that of the control pericardia except for the wavy topology on both the fibrous and serous sides. The average thickness of donkey pericardium (ca. 120 µm) was significantly lower than that from bovine (375 µm) and equine (410 µm), but slightly higher than that from porcine (99 µm) specimens. The interlaced wavy collagen bundles in the pericardium were composed of collagen fibers about 100 nm in diameter. This unique structure ensures that the donkey pericardium has a comparable ultimate tensile strength (UTS) and a much higher failure strain than the commercial pericardia used for the manufacture of heart valves. The donkey pericardium has an organized wavy collagen bundle architecture similar to that of bovine pericardium and has a satisfactory UTS and high failure strain. The thin and strong donkey pericardium might be a good candidate valve leaflet material for TAVI.